2019
DOI: 10.2967/jnumed.119.230003
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric 18F-FDG PET/MRI of the Breast: Are There Differences in Imaging Biomarkers of Contralateral Healthy Tissue Between Patients With and Without Breast Cancer?

Abstract: The rationale was to assess whether there are differences in multiparametric 18 F-FDG PET/MRI biomarkers of contralateral healthy breast tissue in patients with benign and malignant breast tumors. Methods: In this institutional review board-approved prospective single-institution study, 141 women with imaging abnormalities on mammography or sonography (BI-RADS 4/5) underwent combined 18 F-FDG PET/MRI of the breast at 3T with dynamic contrastenhanced MRI, diffusion-weighted imaging, and the radiotracer 18 F-FDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…Although the number of patients in our study was not sufficiently powered to exclude differences, the findings were well in line with immunohistochemical data on consistent FAP expression in breast cancer samples independent of tumor type (13). Background uptake in healthy breast tissue correlated with young age and dense breasts but only slightly higher than published data at 18 F-FDG-PET/MRI (eg, mean SUV max = 1.8 [range, 0.9-4.6]) (23).…”
Section: Discussionsupporting
confidence: 85%
“…Although the number of patients in our study was not sufficiently powered to exclude differences, the findings were well in line with immunohistochemical data on consistent FAP expression in breast cancer samples independent of tumor type (13). Background uptake in healthy breast tissue correlated with young age and dense breasts but only slightly higher than published data at 18 F-FDG-PET/MRI (eg, mean SUV max = 1.8 [range, 0.9-4.6]) (23).…”
Section: Discussionsupporting
confidence: 85%
“…We observed inter-patient heterogeneity in the contralateral breast background signal in both modalities, which resulted in minimal difference in tumor-background ratio following normalization by the contralateral breast in wbPET. Similar variation in background parenchymal FDG uptake have been observed in other studies 24 , 25 . While limiting the PET scans at the early follicular phase of the menstrual cycle may minimize the background parenchymal signal 26 , the patient’s treatment planning should be taken into consideration for scheduling without imposing additional burden.…”
Section: Discussionsupporting
confidence: 88%
“…A few studies have already demonstrated the potential of integrated PET/MR imaging for local and whole-body staging as well as treatment monitoring of sarcoma patients [ 14 , 22 , 23 ]. Furthermore, this new hybrid imaging modality enables simultaneous acquisition of certain quantitative imaging parameters, reflecting different aspects of the underlying tumor biology [ 24 , 25 ]. It has previously been reported that histopathological response can be predicted based on changes in the metabolic activity of the tumors under neoadjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%